Dual stable isotope characterization of excess methane in oxic waters of a mesotrophic lake. (28th July 2020) - Tsunogai, Urumu; Miyoshi, Yuko; Matsushita, Toshiyuki; Komatsu, Daisuke D.; Ito, Masanori; Sukigara, Chiho; Nakagawa, Fumiko; Maruo, Masahiro
Abstract: To determine the source of excess methane in oxic, surface‐water columns often found in freshwater environments, we measured the in situ concentration and stable isotopic compositions (δ 13 C and δ 2 H) of methane in Lake Biwa, a mesotrophic lake in Japan. The values from the littoral zone and lake‐floor sediments were determined, besides those in the water column of the pelagic zone. Furthermore, we conducted incubation experiments to measure microbial oxidation rates and alterations in the isotopic signatures of methane. We found significant vertical and seasonal variations in both in situ concentrations and stable isotopic compositions of methane measured in the pelagic zone. We concluded that active microbial oxidation was primarily responsible for the variation in δ 13 C and δ 2 H values of methane in the pelagic water column. As a result, we defined a new indicator Δ(2, 13) to characterize the sources of dissolved methane, in which variations in both δ 13 C and δ 2 H during methane oxidation had been corrected. The excess methane in oxic, surface‐water columns exhibited Δ(2, 13) values similar to those in the littoral zone. We concluded that excess methane at the surface of the pelagic zone originated from the littoral zone via lateral transport. Anoxic near sediments and inflowing rivers were responsible for methane enrichment in water of the littoral zone and in the surface water columns of the pelagic zone.